Some aspects of enhancement of compulsory liability insurance of operators of the airports and subjects of Ground handling services - Спасибо, В. В. (Theory and practice of jurisprudence, 2016)
In article separate aspects of compulsory aviation insurance of responsibility of operators of the airports and subjects of Ground handling services are opened, the problems connected using such type of insurance are outlined and ways of their permission with use of the project of a new Order and rules of carrying out compulsory aviation insurance of the civil aviation are offered.